2013
DOI: 10.1007/s10803-013-1941-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Peer Support Intervention for Promoting Academic Engagement of Students with Autism in General Education Settings

Abstract: Students with autism spectrum disorder (ASD) have been shown to benefit from being educated in general education classrooms that provide interactions with typically developing peers. However, behaviors exhibited by students with ASD frequently lead to their return to segregated special education settings. Evidence-based interventions that are both cost-efficient and easy to use in general education settings are needed. The purpose of this study was to evaluate the effects of a simple peer support intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 25 publications
1
40
0
1
Order By: Relevance
“…Specifically, children with ASD may need help to manage daily routines, make transitions between activities and engage in social interactions [5]. If these special needs are not addressed, they can result in interruptions during class that decrease learning opportunities, not only for the student with ASD, but also for all the students [20].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, children with ASD may need help to manage daily routines, make transitions between activities and engage in social interactions [5]. If these special needs are not addressed, they can result in interruptions during class that decrease learning opportunities, not only for the student with ASD, but also for all the students [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results showed that students with high autistic traits with much social support could help each other more easily and, based on this, peer support groups for students with ASD in universities are appropriate. Few studies have examined the effectiveness of peer support groups for adolescents or adults with ASD, while there is a lot of support for the effectiveness of peer support groups for young people with ASD (McCurdy & Cole, 2014;Rodriguez-Medina, Martín-Antón, Carbonero, & Ovejero, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There are three reasons why peer support of students with ASD has received academic attention. First, peer support could help students with ASD to improve their academic learning and social skills (VanBergeijk, Klin, & Volkmar, 2008;McCurdy & Cole, 2014;Watkins, O' Reilly, Kuhn, Gevarter, Lancioni, Sigafoos, & Lang, 2015). VanBergeijk et al (2008) pointed out that students with ASD did not have enough opportunities to learn about academic learning and social skills, and needed empirical support about these skills.…”
Section: Peer Supportmentioning
confidence: 99%